Werewolves and Lycanthropus in Selected Slavic Prose of the 19th Century - Ajdačić , Dejan (Poznańskie Studia Slawistyczne, 2021)
The author analyzes the origins and characteristics of werewolves (human-wolves) and lycanthropus (human-dogs) as dual-natured beings within Slavic folk beliefs. He also analyzes the way their mythological properties transform through literature. The werewolf’s mythos is approached through texts of 19th century authors, Russians Orest Somov (Oboroten: narodnaja skazka, 1829) and Alexander Kuprin (Serebrjanyj volk, 1901) and the Pole from Belarus Jan Barszczewski (Wilkołak, 1844), while the lycanthrope’s is viewed through the lens of the literary fairy tale by Serbian Joksim Nović Otočanin (Vrzino kolo i Zlatni i Alem-grad, 1864). The author puts focus on symbolism, specifically that of the human-beast dichotomy. The literary representation of this man-beast duality in 19th century Slavic written prose indicates a fantasy view of the coexistence between beast and man – the beastly in men, or the human in beasts.